Considering multiple types of children’s communities ought to be a priority when designing schools - Mie Guldbæk Brøns (IUL Research)
In this paper, the author reflects on the affordances of various physical learning spaces. The author uses four different types of children’s communities as a lens to do so. Children’s communities are important because they are fundamental for children’s well-being and development. Furthermore, learning to gain access to and partake in communities are skills that are needed throughout life. Teachers are responsible for ensuring that students can access and engage in a variety of communities. Different spaces support different aspects of the professional facilitation of children’s communities. Essentially, school architecture and learning space design support and/or hinder teachers’ pedagogical possibilities.